Regulasi Pencemaran Nama Baik dan Penghinaan melalui Media Teknologi Informasi Komunikasi Pasca Amandemen Undang-Undang ITE - Darnyarsa, I Kadek Bayu Putera; Lathif , Nazaruddin (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2026)
This study examines the issue of defamation and insult through information and communication technology (ICT) media in Indonesia, particularly following the amendment of the Electronic Information and Transactions Law (UU ITE). The primary focus is to evaluate the effectiveness of existing legal frameworks in protecting individuals from acts that harm one’s reputation or honor through digital media. The 2016 amendment to the UU ITE aimed to balance freedom of expression with legal protection for individuals. However, challenges persist in its implementation, including ambiguity in the definition of defamation, the potential misuse of UU ITE provisions, and the public's limited understanding of legal boundaries on social media. This study adopts a normative legal approach by analyzing relevant regulations, including the UU ITE and the Indonesian Penal Code, while comparing these to policies in other countries. Findings indicate that the existing legal mechanisms provide a foundation for individual rights protection but often face obstacles, such as the misuse of defamation clauses to suppress public criticism. Additionally, the government has proposed alternative solutions, including restorative justice approaches and digital literacy programs to enhance public legal awareness. This study recommends drafting clearer regulations and enforcing laws transparently so that freedom of expression and individual protection can coexist harmoniously. Emphasis is also placed on the importance of digital ethics education to prevent violations in the cyberspace domain.